The Effect of Taburia Supplementation on Weight Gain and Nutrient Intake among Underweight Children Aged 6–24 Months in the Working Area of Karang Jati Health Center - Fetmi Fetmi; Astri Ayu Novaria; Riana Pangestu Utami (Journal of Community Nutrition Intervention, 2025)
Underweight in toddlers remains both a global and national health issue. In Balikpapan, the prevalence of underweight increased from 14.1% (2023) to 16.2% (2024). One of the government's efforts to address this problem is through Taburia, a multimicronutrient powder formulated to increase nutritional intake and support growth. However, its effectiveness has never been evaluated locally at the Karang Jati Health Center, Balikpapan City. This study is a quasi-experiment with a one-group pre-test and post-test design involving 30 underweight toddlers aged 6–24 months. The intervention consisted of Taburia administration for 30 days at a dose of 1 sachet every two days. Weight data were measured weekly, while nutrient intake was assessed using a 2x24-hour food recall. Analysis was performed using the Wilcoxon test. The results showed that Taburia administration had a significant effect on increasing the toddlers' body weight (p=0.005). The average weight gain for the 6–11 month age group was 400.0 ± 141.4 grams, and for the 12–24 month group, it was 376.9 ± 127.4 grams. Taburia also significantly increased protein intake (p=0.021) and fat intake (p=0.002), while increases in energy and carbohydrates were not significant (p>0.05). Taburia administration has a positive effect on weight gain and the improvement of protein and fat intake in underweight toddlers aged 6–24 months. This intervention has potential as a public nutrition strategy, especially in areas with a high prevalence of underweight. As a follow-up, the Taburia program needs to be expanded with family nutrition education and long-term monitoring, as well as further research with an RCT design and longer duration to strengthen the evidence of its effectiveness